2015
DOI: 10.3109/21691401.2015.1058807
|View full text |Cite
|
Sign up to set email alerts
|

The role of the bile acid chenodeoxycholic acid in the targeted oral delivery of the anti-diabetic drug gliclazide, and its applications in type 1 diabetes

Abstract: Gliclazide (G) is used to treat type 2 diabetes (T2D), and also has anti-platelet, anti-radical, and anti-inflammatory effects. G has poor water solubility and high inter-individual variations in absorption, limiting its application in type 1 diabetes (T1D). The bile acid, chenodeoxycholic acid (CDCA), has permeation-enhancing effects. Sodium alginate (SA) was used to microencapsulate G and CDCA to produce control (G-SA) and test (G-CDCA-SA) microcapsules. Both microcapsules showed uniform structure, morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In a recent study, when incorporated with matrix formulation, CDCA showed excipient-stabilizing effects on microcapsules carrying viable insulinoma β-cells, in vitro [ 6 ]. In another study in our laboratory, the incorporation of CDCA improved the stability and reduced swelling of drug-loaded microcapsules resulting in improved drug stability and release and overall better shelf-life [ 7 ]. In addition to its potential applications as a stabilizing excipient in formulations, CDCA and other bile acids have also been shown to exert significant pharmacological and biological effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, when incorporated with matrix formulation, CDCA showed excipient-stabilizing effects on microcapsules carrying viable insulinoma β-cells, in vitro [ 6 ]. In another study in our laboratory, the incorporation of CDCA improved the stability and reduced swelling of drug-loaded microcapsules resulting in improved drug stability and release and overall better shelf-life [ 7 ]. In addition to its potential applications as a stabilizing excipient in formulations, CDCA and other bile acids have also been shown to exert significant pharmacological and biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, in the context of drug and islet formulation and delivery, CDCA seems to have strong effects on stabilizing microcapsules containing islets, as well as exerting positive biological effects on islets that may improve their ability to survival and function, post-transplantation [ 6 , 7 ]. Accordingly, in this study, in order to investigate the applications and potential role of CDCA in islet transplantation, healthy islets were harvested from mice, encapsulated in CDCA microcapsules, and surgically transplanted into the epididymal tissues in pelvic region of 6 syngeneic diabetic mice (injected with alloxan to induce T1D, confirmed with blood glucose >16 mM in two consecutive measurements over two days, and absence insulin in blood).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of the polymer is a vital step in drug delivery and discovery, as it affects drug release and absorption [ 49 ]. Sodium alginate (SA) has shown the most promising result in oral drug administration [ 31 , 50 ]. SA is a natural polysaccharide extracted from brown algae and has characteristic features of being biodegradable and biocompatible, and it has demonstrated excellent stability and compatibility, as well as pH-dependant degradation and release kinetics which are also influenced by its viscosity [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to dry the microcapsules, they were taken out of the refrigerator, placed at room temperature for 8 h, followed by being placed at a controlled-hot room for 48 h (at 37 °C and relative humidity of 35%). Relative humidity was set as the weight of water vapour for each unit of weight of air, and was expressed as grams of water vapour per each kilogram of air, using the Angelantoni Environmental and Climatic Test Chamber (Italy), as per our established-methods [ 30 , 31 ]. Imaging, size analysis, and surface composition measurements were carried out simultaneously at multiple research centres including: the Curtin University Electron Microscope Facility at Bentley, the John De Laeter Research Centre and the Pharmaceutical Technology Laboratory, at Curtin University, as well as the CISRO research centre in Perth, Western Australia, using our established methods [ 10 , 29 ].…”
Section: Methodsmentioning
confidence: 99%